2007
DOI: 10.1097/blo.0b013e31805d85c4
|View full text |Cite
|
Sign up to set email alerts
|

Limb Salvage Surgery for Osteosarcoma

Abstract: Successful management of osteosarcoma with limb salvage surgery is a challenging problem in the developing world. We report our early results with low-cost chemotherapy (without methotrexate) and low-cost limb salvage surgery. We prospectively collected data for 135 patients with histologically proven high-grade osteosarcoma of the extremities given neoadjuvant chemotherapy and treated with limb salvage surgery between January 2000 and February 2004. A locally designed and fabricated stainless steel customized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 11 publications
(15 reference statements)
1
32
0
1
Order By: Relevance
“…We chose stainless steel as the material since it was easy to work with and would keep the implant cost low. Our early experience with these prostheses in limb salvage for osteosarcoma was reported in 2007 [1]. A lowcost but technically compromised implant is a reality in many developing countries and not well reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We chose stainless steel as the material since it was easy to work with and would keep the implant cost low. Our early experience with these prostheses in limb salvage for osteosarcoma was reported in 2007 [1]. A lowcost but technically compromised implant is a reality in many developing countries and not well reported.…”
Section: Discussionmentioning
confidence: 97%
“…In the year 2000, with the help of a local implant manufacturer, we began fabricating a very low-cost megaprosthesis to kick-start our limb salvage program [1]. The initial design was primitive and simplistic, but it gradually evolved as we learned from our failures; we had many breakages of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…En las cirugías de salvamento de la extremidad se considera que sus costes y los de una amputación son similares 10,11 , aunque mejore la integración social y autopercepción en las cirugías de salvamento 11,12 . No obstante, conviene considerar las verdaderas ventajas en calidad de vida y que ello justifique el coste en el que se incurre 13 .…”
Section: Discussionunclassified
“…In industrialized countries, the incidence of amputation due to malignancy has decreased from 0.62 per 100,000 people in 1988 to 0.35 per 100,000 people in 1996 [57,58]. In a large multicenter study, Bielack et al reported that the use of ablative surgery (defined as amputations, disarticulations, and rotationplasties) decreased from 60.1% in the 1980s to 31.4% in the 1990s [59].…”
Section: Immunotherapiesmentioning
confidence: 94%